THE EFFECT OF IMPLEMENTING A PROJECT BASED LEARNING MODEL BASED ON LOCAL WISDOM POTENTIAL ON CONCEPT UNDERSTANDING AT SMP NEGERI 3 AIR BATU - Winda Winda; Ella Andhany (FKIP Universitas Muhammadiyah Tangerang, 2026)
This study aims to analyze the effect of the Project Based Learning (PjBL) model based on local wisdom on the understanding of mathematical concepts of junior high school students. The background of this study departs from the need for a more contextual and meaningful learning model in improving mastery of basic mathematical concepts. The research method uses a quasi-experimental design with a Nonequivalent Control Group Design, involving two classes VIII in UPTD SMP Negeri 3 Air Batu, namely class VIII-B as the experimental group and VIII-C as the control group. Data collection instruments are in the form of pretest and posttest, which are then analyzed using N-Gain to determine the improvement in learning outcomes and Independent Sample t-Test to test significant differences between groups. The results showed that the experimental group that received PjBL learning based on local wisdom experienced a higher increase in understanding of mathematical concepts, with an average posttest score of 78.26 and N-Gain 0.52 (medium category). In contrast, the control group obtained an average of 66.82 with N-Gain 0.29 (low category). The t-test results showed a p-value <0.05, thus concluding that local wisdom-based PjBL significantly improved students' understanding of mathematical concepts. Therefore, this model is considered effective in creating relevant, contextual learning, and connecting mathematical concepts to students' daily lives.